2021
DOI: 10.1073/pnas.2011170118
|View full text |Cite
|
Sign up to set email alerts
|

IDO1 scavenges reactive oxygen species in myeloid-derived suppressor cells to prevent graft-versus-host disease

Abstract: Tryptophan-catabolizing enzyme indoleamine 2,3-dioxygenase 1 (IDO1) also has an immunological function to suppress T cell activation in inflammatory circumstances, including graft-versus-host disease (GVHD), a fatal complication after allogeneic bone marrow transplantation (allo-BMT). Although the mononuclear cell expression of IDO1 has been associated with improved outcomes in GVHD, the underlying mechanisms remain unclear. Herein, we used IDO-deficient (Ido1−/−) BMT to understand why myeloid IDO limits the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…IDO-KO mice lack functional MDSCs compared to WT specimens in a model of graft versus host disease [108]. However, direct evidence of IDO expression in M-or PMN-MDSCs is still lacking.…”
Section: Tryptophan Metabolismmentioning
confidence: 99%
“…IDO-KO mice lack functional MDSCs compared to WT specimens in a model of graft versus host disease [108]. However, direct evidence of IDO expression in M-or PMN-MDSCs is still lacking.…”
Section: Tryptophan Metabolismmentioning
confidence: 99%
“…Novel aspects of IDO1 biology that potentially influence its role as drug target in cancer, infectious diseases, autoimmunity, and neurodegeneration continue to be discovered, such as its regulation by heme availability, 13 its activation by polysulfides, 14 its nitrite reductase activity, 15 its involvement in the redox signaling pathways of hydrogen peroxide and singlet oxygen, 16,17 and its reactive oxygen species scavenging activity. 18 Therefore, there is an ongoing interest in IDO1's biology and pharmacological inhibitors capable of modulating these different pathways and processes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…IDO1’s interaction sites with Src homology 2 domain phosphatases (SHPs), phosphoinositide 3-kinases (PI3Ks), and suppressor of cytokine signaling 3 (SOCS3) are all localized in the small domain and are distinct from the enzymatic active site in the large domain (Figure A). Novel aspects of IDO1 biology that potentially influence its role as drug target in cancer, infectious diseases, autoimmunity, and neurodegeneration continue to be discovered, such as its regulation by heme availability, its activation by polysulfides, its nitrite reductase activity, its involvement in the redox signaling pathways of hydrogen peroxide and singlet oxygen, , and its reactive oxygen species scavenging activity . Therefore, there is an ongoing interest in IDO1’s biology and pharmacological inhibitors capable of modulating these different pathways and processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have demonstrated the protective role of IDO1 in graft-versus-host disease (GVHD) (30,31). A recent study suggested that myeloid-derived IDO1 had the ability to improve GVHD survival (32). GBP2 was a commonly used gene that distinguished non-rejection and rejection kidney allografts (33).…”
Section: Discussionmentioning
confidence: 99%